2016
DOI: 10.1002/masy.201650011
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties and Intermolecular Interaction of Blends of Poly(ethylene oxide) and Poly(methyl acrylate)

Abstract: Summary Polymer blends of poly(ethylene oxide) (PEO) and poly(methyl acrylate) (PMA) were prepared by solution casting method. Thermal stability of the binary PEO/PMA blends was examined by termogravimetric analysis (TGA). Decomposition temperatures of the binary blends were estimated from the onsets of the weight loss curves of TGA thermograms. The decomposition temperatures of the blends increase when the content of PEO elevates. Hence, PEO has a better thermal stability as compared to PMA. The activation en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
(35 reference statements)
2
13
0
Order By: Relevance
“…Refering to Figure (a), there is no significant shifting of the wavenumbers noted of the triplet of v (C‐O‐C) mode at 1144, 1094 and 1059 cm −1 for neat PEO until W PEO ≤ 0.2, they shift to 1155 cm −1 as the centre absorption band and to 1194 and 1118 cm −1 as the two shoulders. FTIR study suggests that the miscibility of PEO/PMA blends may not be due to any specific intermolecular interaction between the components, but only weak intermolecular interaction [ i.e., This suggestion is supported by studies reported in the literature . It may due to entropy effect instead of by enthalpy effect] between PEO and PMA in the blends.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Refering to Figure (a), there is no significant shifting of the wavenumbers noted of the triplet of v (C‐O‐C) mode at 1144, 1094 and 1059 cm −1 for neat PEO until W PEO ≤ 0.2, they shift to 1155 cm −1 as the centre absorption band and to 1194 and 1118 cm −1 as the two shoulders. FTIR study suggests that the miscibility of PEO/PMA blends may not be due to any specific intermolecular interaction between the components, but only weak intermolecular interaction [ i.e., This suggestion is supported by studies reported in the literature . It may due to entropy effect instead of by enthalpy effect] between PEO and PMA in the blends.…”
Section: Resultssupporting
confidence: 68%
“…From previous study, blending of PEO ( T g ∼ −52 °C) with PMA ( T g ∼ 13 °C) is miscible for the entire composition . The T g s of the blends are below room temperature (∼25 ° C), which are suitable to be the polymer hosts of SPE …”
Section: Introductionmentioning
confidence: 94%
“…For PEO-blend based SPEs, PEO shows miscibility with some polyacrylates. Polyacrylates such as poly(methyl methacrylate) (PMMA), [4,53,54] poly(methyl acrylate) (PMA), [55][56][57] polyacrylate copolymer (PAc) [58,59] are miscible with PEO at low content of inorganic salt (<15 wt%). PEO is immiscible with poly(n-butyl methacrylate) (PnBMA).…”
Section: Introductionmentioning
confidence: 99%
“…Data is retrieved from (Zainal et al, 2017). Table 3 lists the E a quantities for different systems estimated using the Hoffman's Arrhenius-like relationship, retrieved from (Halim, Chan, & Sim, 2016;Zainal et al, 2017).…”
Section: Thermogravimetrymentioning
confidence: 99%